Reception of the Integration of Islam and Science: A Case Study at Islamic Institute of Kediri - Alamin, Taufik; Mujib, Abdul; Sulaeman, Mubaidi; Nasution, Alhafidh (Tribakti: Jurnal Pemikiran Keislaman, 2024)
The enduring dichotomy between religion and science rooted in historical conflicts during the heyday of Islam and the Western Renaissance has persistently challenged efforts to reconcile the two. In Indonesia, thinkers within State Islamic Higher Education (PTKIN) have proposed the integration-interconnection perspective to bridge this gap. However, after almost two decades, this approach has remained unfamiliar to PTKIN students, including those at Kediri State Institute of Islam. This study aims to assess the reception of PTKIN academics, particularly students from the Faculty of Ushuluddin and Da'wah at Kediri State Institute of Islam, towards the integration of Islam and science, from a Quranic perspective. Conducted as a field research, this study employs a mixed-method approach that combines both quantitative and qualitative methods. This methodological choice sought to provide a more comprehensive understanding of the phenomenon under investigation. This study focuses on the academic community of Kediri State Institute of Islam. The findings reveal that the majority of students in the Faculty of Ushuluddin and Da'wah at Kediri State Institute of Islam perceived a limited correlation between Islam and science. Their understanding diverges significantly from the intended goals of Islam and science integration at Kediri State Institute of Islam. The Islam and Science course offered by the faculty has emerged as a valuable platform for academics and da'wah activists to communicate the concept of integrating Islam and science to their students and broader community. Emphasizing the need for innovative learning modules related to Islam and Science, this study suggests that this approach can facilitate a deeper appreciation of the interconnection integration among PTKIN students. Ultimately, these efforts aim to overcome the persistent dichotomy between religion and science.